Influence of Learning Styles on Male and Female Science Education Distance Learning Students of NOUN and their Attitudes towards E-Learning - Timothy, James; Owolabi, Tunde (West African Journal of Open and Flexible Learning, 2014)
The main purpose of this research was to investigate the impact of learning styles and attitudes towards e-leaning environment with reference to Masters in Science Education students of the National Open University of Nigeria. All the Masters in Science Education students of the National Open University of Nigeria formed the population for this study. Seventy (70) students were randomly selected from the population through balloting (n=70). Survey designed was used for the study through questionnaires. Learning style questionnaire developed by Honey and Mumford (1992) was used to determine the learning style of Science Education students of NOUN undergoing Masters in Science Education (M.Ed. Sc. Ed). Attitudinal questionnaire was later administered to the subjects. The results indicate that attitudes of science students towards e-leaning have a strong positive correlation with their learning styles. The findings of this study have practical implications for educators and designers of e-leaning programmes of higher institutions. Based on the findings from this research, it was recommended that science teachers should provide both synchronous and asynchronous activities during science teaching. This will enhance meaningful learning through e-leaning. It is also recommended that science teachers should identify the learning styles of their students and pattern their teaching towards it.